2023
DOI: 10.3390/insects14070604
|View full text |Cite|
|
Sign up to set email alerts
|

Seasonal Dynamics of Aphid Flights and Cotton Leafroll Dwarf Virus Spread in Alabama

Jessica B. Mahas,
Charles Ray,
Adam Kesheimer
et al.

Abstract: Cotton leafroll dwarf virus (CLRDV) is an introduced Polerovirus (Family: Solemoviridae) of cotton, Gossypium hirsutum L., in the U.S. The only vector known to transmit this virus to cotton is the cotton aphid, Aphis gossypii Glover; however, there are seven other species of aphids (Hemiptera: Aphididae) reported to colonize cotton in the southeastern U.S.: Protaphis middletonii (Thomas), Rhopalosiphum rufiabdominale (Sasaki), Aphis craccivora Koch, Macrosiphum euphorbiae Thomas, Myzus persicae (Sulzer), Smyth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 29 publications
1
1
0
Order By: Relevance
“…Populations of P. middletonii have been observed to peak earlier in the cotton-growing season than A. gossypii [35]. Mahas et al, 2022, also showed that some CLRDV spread coincided with the peak flights of P. middletonii, which was also observed in our companion manuscript [52]. These observations provide rationale for testing the vector competence of this species, but it would not help to explain why the high incidence of CLRDV appears to be restricted to southern portions of Alabama and Georgia.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Populations of P. middletonii have been observed to peak earlier in the cotton-growing season than A. gossypii [35]. Mahas et al, 2022, also showed that some CLRDV spread coincided with the peak flights of P. middletonii, which was also observed in our companion manuscript [52]. These observations provide rationale for testing the vector competence of this species, but it would not help to explain why the high incidence of CLRDV appears to be restricted to southern portions of Alabama and Georgia.…”
Section: Discussionsupporting
confidence: 78%
“…Such information is valuable in the context of understanding the epidemiology of CLRDV, because it shows a greater abundance of the vector in areas with a higher reported incidence of CLRDV. A companion study examining CLRDV spread in relation to aphid flights in southern AL, central AL, and northern AL showed that virus spread was detected over a greater number of weeks in southern and central AL than northern AL, where fewer A. gossypii were observed [52]. Resources were not available to monitor virus spread at all sampled locations; however, taken together, the results of these studies show that the primary vector of CLRDV has a variable abundance from VA to TX.…”
Section: Discussionmentioning
confidence: 99%